Resource Extraction when a Future Substitute has an Uncertain Cost - Hoel, M. (Review of Economic Studies, 1978)
Journal Article Resource Extraction when a Future Substitute has an Uncertain Cost Get access Michael Hoel Michael Hoel University of Oslo Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 637–644, https://doi.org/10.2307/2297265 Published: 01 October 1978 Article history Received: 01 January 1977 Accepted: 01 November 1977 Published: 01 October 1978